Pengaruh Lingkungan Kerja Terhadap Produktivitas Karyawan Pada PT. Lonsum Balombissie Di Kabupaten Bulukumba - Musakkir Basri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The influence of the work environment on employee productivity in a company makes it very possible to determine success. The work environment has a significant influence on a company, so knowledge is needed to make achievements according to the company's goals. Also, this also has several aspects for employees to meet the company's needs so that losses do not occur. Based on the results of hypothetical measurements, the work environment partially has a positive and significant effect on employee productivity at PT Lonsum Balombissie in Bulukumba Regency. In general, the most significant influence on employee performance at PT Lonsum is a healthy work environment that is in accordance with logical control.